Depletion of Neutrophils Exacerbates the Early Inflammatory Immune Response in Lungs of Mice Infected with Paracoccidioides brasiliensis (2016)
ABSTRACT: Neutrophils predominate during the acute phase of the Paracoccidioides brasiliensis infection. Herein, we determined the role of the neutrophil during the early stages of experimental pulmonary paracoccidioidomycosis using a monoclonal antibody (mAb) specific for neutrophils. Male BALB/c mice were inoculated intranasally with 1.5 × 106 or 2 × 106 P. brasiliensis yeast cells. The mAb was administered 24 h before infection, followed by doses every 48 h until mice were sacrificed. Survival time was evaluated and mice were sacrificed at 48 h and 96 h after inoculation to assess cellularity, fungal load, cytokine/chemokine levels, and histopathological analysis. Neutrophils from mAb-treated mice were efficiently depleted (99.04%). Eighty percent of the mice treated with the mAb and infected with 1.5 × 106 yeast cells died during the first two weeks after infection. When mice were treated and infected with 2 × 106 yeast cells, 100% of them succumbed by the first week after infection. During the acute inflammatory response significant increases in numbers of eosinophils, fungal load and levels of proinflammatory cytokines/chemokines were observed in the mAbtreated mice. We also confirmed that neutrophils are an important source of IFN- and IL-17. These results indicate that neutrophils are essential for protection as well as being important for regulating the early inflammatory immune response in experimental pulmonary paracoccidioidomycosis.